43 Studies on the immunomodulatory activity of Lonicerae japonicae flos extracts in the hydrocortisone-induced immunosuppressed mouse model. (19th December 2016) - Wang, Liang; Lv, Xiaodan; Liu, Yumeng; Zhao, Xi; Wang, Di; Zhang, Jianhui
Abstract : Objectives: Lonicerae japonicae flos is widely applied to improve the human immune system in Chinese traditional medicine. However, there are few systematic pharmacodynamic and pharmacological studies of L. japonicae flos extracts (LF). Our present study aimed to evaluate the immunomodulatory activity of LF and its underlying mechanisms in an immunosuppressed mouse model. Methods: LF (50, 100 and 200 mg/L of chlorogenic acid) was administered for 31 days. From the 10th day, hydrocortisone (HC, 4 mg/kg) was administered as an immunosuppressant. The spleen index, body weight, lymphocyte proliferation assay, cytotoxic activity assay of natural killer cells, ELISA assay and Western blotting assay were used to assess the immunomodulatory activity of LF. Results: LF strongly ameliorated the reduction in the spleen index and body weight caused by HC. After 200 mg/L LF treatment, NK cell activity increased by 28.3% and T lymphocyte proliferation was upregulated by 17.8% compared with the HC group. Serum levels of IL-1, IL-2, IL-6, TNF-α and nitric oxide (NO) were significantly enhanced by LF. Increased expression of nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) and inducible nitric oxide synthase (iNOS) was noted in spleen lysates after LF treatment. Conclusions: L. japonicae flos extracts exert immumodulatory activity by improving cellular as well as innate immunity in immunosuppressed mice and promoting the secretion of immune-related cytokines via iNOS-related signaling pathways.